2005
DOI: 10.1109/tasc.2005.849219
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual approach to the ultimate low AC loss YBCO Superconductor

Abstract: Wide tapes of YBCO coated conductors make minimization of ac loss very difficult. Subdivision of the tape into narrow filaments does not provide complete transposition when twisted and current sharing is not equalized due to inductance differences. For ac power applications operating near 400 Hz for military aircraft power systems, equal inductance filaments and short twist pitch are very important to loss minimization. A fully transposed YBCO tape that approximates a Rutherford cable has been conceived to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…This is important because it is reported in the literature that the hysteresis losses will be decreased by the inverse of the number of lines (1/N a ) in comparison with a completely covered substrate [15,22]. The currently reported width for patterns is going from 30 µm up to one millimeter when using lithography or etching methods [7,8,12,11,16,19,21,22,24]. With our ink-jet printing technique we can obtain a similar lateral resolution in only one processing step.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This is important because it is reported in the literature that the hysteresis losses will be decreased by the inverse of the number of lines (1/N a ) in comparison with a completely covered substrate [15,22]. The currently reported width for patterns is going from 30 µm up to one millimeter when using lithography or etching methods [7,8,12,11,16,19,21,22,24]. With our ink-jet printing technique we can obtain a similar lateral resolution in only one processing step.…”
Section: Discussionmentioning
confidence: 81%
“…There will always be eddy current losses associated with substrate and stabilization layers, which can be reduced by maximizing the substrate resistance and by also striating the stabilization layer. These methods, and avoiding interfilamentary bridging, also reduce coupling currents; but twisting the conductor, or ideally fully transposing the filaments, is required to minimize coupling losses [10][11][12][13][14][15][16][17][18]. This filamentary superconducting structure can be accomplished through several techniques which can be divided into two main approaches: with or without material removal.…”
Section: Introductionmentioning
confidence: 99%
“…Another method to reduce the AC loss of HTS CCs is to change their physical arrangements, e.g., the Roebel concept [217][218][219], Rutherford cable [220,221], and Conductor on Round Core (CORC ® ) wire [222][223][224]. The Roebel cable concept was proposed by Ludwig Roebel in 1914 to produce a low-loss copper cable [224].…”
Section: Roebel Rutherford-type and Corc ® Cablesmentioning
confidence: 99%
“…To minimize the high-frequency coupling loss, the Rutherford cable structure has been proposed by Wilson, which does not require complex twist geometries [220]. It has been demonstrated that the Rutherford configuration is a promising candidate to realize the ultimate low AC loss [221]. The conventional Rutherford-type cabling technique is suitable for round strands of superconductors [226], e.g., BSCCO-2212 and NbTi wires, as shown in Figure 16b.…”
Section: Roebel Rutherford-type and Corc ® Cablesmentioning
confidence: 99%
“…However, filament patterning is still in its infancy, and many aspects still need to be ironed out. An additional aspect that needs attention is the need for filament twisting or, preferably, transposition [6]- [8]. Twisting is not really practical in a tape-shaped wire needing to be wound into compact coils of various shapes.…”
Section: Introductionmentioning
confidence: 99%